2018
DOI: 10.1002/ptr.6065
|View full text |Cite
|
Sign up to set email alerts
|

Antiadipogenic effects of a standardized quassinoids‐enriched fraction and eurycomanone from Eurycoma longifolia

Abstract: Bioactive compounds of Eurycoma longifolia (EL) jack were previously shown to reduce omentum fat mass and oestradiol-induced fatty uterine adhesion in rats. However, the exact role of EL on adipogenesis remains unknown. This study sought to investigate the effects of an EL standardized quassinoids-enriched fraction (SQEL) and the pure compound, eurycomanone, on adipogenesis in 3T3-L1 preadipocyte cells. 3T3-L1 cells were induced to differentiate and treated for 8 days. The treatment reduced intracellular accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…An in vivo study also demonstrated the efficacy of this plant. The study found that a standardized quassinoid-enriched fraction of E. longifolia reduced body weight gain, adipose tissue hypertrophy, and serum glycerol levels in mice with HFD induced obesity [16]. Furthermore, clinical testing illustrated that consumption of the E. longifolia extract together with exercise enhanced lipolysis [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An in vivo study also demonstrated the efficacy of this plant. The study found that a standardized quassinoid-enriched fraction of E. longifolia reduced body weight gain, adipose tissue hypertrophy, and serum glycerol levels in mice with HFD induced obesity [16]. Furthermore, clinical testing illustrated that consumption of the E. longifolia extract together with exercise enhanced lipolysis [14].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, E. longifolia roots displayed low pancreatic lipase-inhibitory activity but strong potential to enhance lipolysis and reduce lipid accumulation in 3T3-L1 adipocytes. E. longifolia is a well-known medicinal plant in the Asian region, and several studies have described the potential of its roots to treat obesity [14][15][16]. For instance, our research group previously explored the bioactive compounds of E. longifolia roots and their lipolysis-enhancing activities in a cell-based assay [15].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of PKA phosphorylation has been identified in obese samples and closely related to lipid metabolism disorders [38][39][40]. [45][46][47][48] have shown that the expression of PKA, HSL and cAMP mRNA is upregulated following EN treatment, while AKT expression is downregulated. However, in this study, we found that expression of PKA, HSL, cAMP and AKT were upregulated at both the mRNA and protein levels following EN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that a newly identified intracellular fat-specific phospholipase A2 (AdPLA) interferes with lipolysis by regulating the production of arachidonic acid [21,22]. for future pharmacokinetic studies of the efficacy and safety of EN [26][27], metabolite research in vivo [28], toxicology [29][30], lipolysis and improvement of hypertension [31][32][33]. At present, there are a lot of theories related to lipolysis that have been supported in a large number of animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have revealed a number of phytoconstituents or extracts having the potential to counteract obesity. Among these, plumbagin, dehydroleucodine, eurycomanone from Eurycoma longifolia , phytocannabinoids, genipin from Gardeniae fructus , lignans from Faructus arctii , saringosterol isolated from Sargassum muticum , anthocyanidin‐rich Vitis vinifera grape skin extract, pterostilbene, Pinus koraiensis leaf alcoholic extract, Momordica charantia , and Salvia miltiorrhiza extract (Abood, Veisaga, López, & Barbieri, ; Balan, Chan, Murugan, AbuBakar, & Wong, ; da Costa et al, ; Gao et al, ; Gomez‐Zorita et al, ; Gong, Zhang, & Xu, ; Guan et al, ; Hong et al, ; Lee, Cho, Hong, & Ahn, ; Leng et al, ; Pai, Martis, Joshi, Munshi, & Juvekar, ; Ramlugon, Levendal, & Frost, ). This virtual issue, as well as two previous virtual issues on the clinical efficacy of herbal nutraceuticals (Izzo, ) and on the pharmacology of curcumin (Izzo, ), is free available at https://onlinelibrary.wiley.com/journal/10991573.…”
mentioning
confidence: 99%